2016
DOI: 10.1002/msc.1141
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcomes of Multidisciplinary Rehabilitation for Chronic Musculoskeletal Pain

Abstract: Improvements in pain and functioning seen directly after a 15-week multidisciplinary treatment programme for patients with CMP were maintained, health care usage decreased and the number of working hours among working patients increased at 24 months' follow-up. Future studies are needed to examine if additional interventions after discharge can enhance further the favourable results. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
3
18
0
1
Order By: Relevance
“…Our findings are mostly consistent with several systematic reviews, which have concluded that IMPR generally is effective, but with small to moderate effects [ 7 , 8 , 9 , 10 , 13 ]. They are also in line with previous primary studies reporting long-term improvements on pain and quality of life [ 40 , 41 ]. In contrast, an umbrella review from 2018 assessing the strength of the evidence for the effectiveness of IMPR concluded that there is currently no robust evidence for the effectiveness of IMPR in any outcome, with the possible exception of decreased pain short term [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are mostly consistent with several systematic reviews, which have concluded that IMPR generally is effective, but with small to moderate effects [ 7 , 8 , 9 , 10 , 13 ]. They are also in line with previous primary studies reporting long-term improvements on pain and quality of life [ 40 , 41 ]. In contrast, an umbrella review from 2018 assessing the strength of the evidence for the effectiveness of IMPR concluded that there is currently no robust evidence for the effectiveness of IMPR in any outcome, with the possible exception of decreased pain short term [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…The present cohort was considered to be a representative chronic musculoskeletal pain sample, with similar demographics to patients normally participating in IMPR programs both in Sweden and other Western countries as presented in other studies [ 8 , 9 , 10 , 41 ]. Since the present study targeted patients in specialist care, the external relevance extends to patients in specialist care units rather than to subjects seen in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the expected dependencies of patients within each of the 5 participating treatment locations, we applied the Donner et al [ 55 ] formula for the variance inflation factor, assuming an intracorrelation coefficient of 0.2 [ 56 , 57 ]. Furthermore, we corrected the analysis for an expected attrition of 20%, which is based on the average attrition of similar studies that used the PDI [ 21 , 58 , 59 ]. Based on these calculations, a minimum sample size of 157 participants, equally divided over 5 treatment locations, will be required.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the expected dependencies of patients within each of the 5 participating treatment locations, we applied the Donner et al [55] formula for the variance inflation factor, assuming an intracorrelation coefficient of 0.2 [56,57]. Furthermore, we corrected the analysis for an expected attrition of 20%, which is based on the average attrition of similar studies that used the PDI [21,58,59]. Based on these calculations, a minimum sample size of 157 participants, equally divided over 5 treatment locations, will be required.…”
Section: Sample Size Calculationmentioning
confidence: 99%